TEACHING BASIC CONCEPTS OF CRYPTOGRAPHY IN PROFESSIONAL HIGH SCHOOL - Melo Marin, Regina Paiva; Soares Souza, Jackson Gomes [UNESP]; Gallegos Marin, Luciano Heitor (Unesp-faculdade Ciencias & Letras, 2021)
The cryptography is present in several operations performed daily by people, such as online shopping or in dialogues using computer equipment and the Internet as a proxy. Although cryptography is very important in the contemporary context, the teaching of the cryptography subject is new for students of professional high school. In this regard, one of the biggest challenges is to motivate students in using the cryptographic methods in the classroom. The objective of this work is to investigate the use and learning of cryptography by students of professional high school. For this purpose, the Survey methodology was used with self-evaluated questions about the motivation, understanding and the use of computational tools containing basic cryptography concepts. An analysis of the responses suggests that most students find the cryptography subject difficult to learn, but all them were able to practice and learn at least one of the cryptographic techniques taught.
Keywords: Practices; Teaching; Learning; Cryptography